Analisis Usahatani Padi di Selogiri Wonogiri - Nila Nur Rohmaniyah; Titik Ekowati; Wahyu Dyah Prastiwi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
Farming activities are a source of farmers' income and are expected to be profitable or provide maximum profits to implement business sustainability. The aim research was to analyze the profitability and factors that influence the income of rice farming in Selogiri. The study was conducted from January – March 2022. The research location was in Selogiri District, Wonogiri Regency, which was chosen purposively because it has the highest rice area in Wonogiri Regency. Survey methods were used in the research, with 96 farmers selected as respondents. The types of data used were primary and secondary. Preliminary data were taken from interviews with farmers in Selogiri District consisting of production costs, investment, and respondent data. Secondary data were of BPS data, journals, and literacy taken from the internet, including the research location's general condition, population data, maps, and bank deposit interest rates. Data were analyzed by analyzing profitability and multiple linear regression analysis. They showed that farming is profitable, with a profitability value of 77.86% and a BRI bank interest rate of 2.3%. Prices of seeds, fertilizers, pesticide labor wages, irrigation prices, and land rents simultaneously affect income. In contrast, fertilizer prices, labor wages, and irrigation prices partially affect income.